2018
DOI: 10.1038/s41401-018-0064-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activation of REV-ERBα represses LPS-induced microglial activation through the NF-κB pathway

Abstract: REV-ERBα, the NR1D1 (nuclear receptor subfamily 1, group D, member 1) gene product, is a dominant transcriptional silencer that represses the expression of genes involved in numerous physiological functions, including circadian rhythm, inflammation, and metabolism, and plays a crucial role in maintaining immune functions. Microglia-mediated neuroinflammation is tightly associated with various neurodegenerative diseases and psychiatric disorders. However, the role of REV-ERBα in neuroinflammation is largely unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 35 publications
4
70
0
Order By: Relevance
“…The NF-κB pathway is a critical regulator of innate immune activation which interacts with Rev-erbα (21,28). We observed up-regulation of several genes involved in the positive regulation of NF-κB signaling, such as Nfkb2, Tlr4, Stat3, and Traf2, as well as down-regulation of two genes involved in inhibiting NF-κB signaling (Nfkbib and Usp31) ( Fig.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The NF-κB pathway is a critical regulator of innate immune activation which interacts with Rev-erbα (21,28). We observed up-regulation of several genes involved in the positive regulation of NF-κB signaling, such as Nfkb2, Tlr4, Stat3, and Traf2, as well as down-regulation of two genes involved in inhibiting NF-κB signaling (Nfkbib and Usp31) ( Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Because it is a nuclear receptor, Rev-erbα is an attractive therapeutic target which can be modulated with available small-molecule agonists and antagonists (19,20). While the function of Rev-erbα in neuroinflammation and neurodegeneration has not been directly examined, Rev-erb agonist drugs appear to prevent inflammation and cell death when infused into the brain (21). Thus, we have examined the role for Rev-erbα in the control of neuroinflammation, using genetic and pharmacological manipulations both in vivo and in vitro.…”
mentioning
confidence: 99%
“…The MAPK and NF-κB pathways are implicated in the control of synovial inflammation, hyperplasia, matrix degeneration, and bone destruction. There is a close correlation between NF-κB and NR1D1 16,32 . NR1D1 regulates experimental colitis by repressing the NF-κB/ NLRP3 axis 16 .…”
Section: Discussionmentioning
confidence: 83%
“…NF-κB plays a key role in regulating the immune response to infection (Guo et al 2019). LPS has been shown to promote microglial activation and neuroinflammatory response by activating NF-κB through their specific receptors (TLR4) (Guo et al 2019). Our data showed that ASA Ⅵ inhibited the LPS-induced phosphorylation of NF-κB in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 67%
“…NF-κB is found in almost all animal cell types and is involved in cellular responses to stimuli such as stress, cytokines, and bacterial or viral antigens (Pan et al 2017). NF-κB plays a key role in regulating the immune response to infection (Guo et al 2019). LPS has been shown to promote microglial activation and neuroinflammatory response by activating NF-κB through their specific receptors (TLR4) (Guo et al 2019).…”
Section: Discussionmentioning
confidence: 99%